Understanding the association between unmet dental care needs and household food security status among older people in Ghana - Daniel Amoak; Joseph Asumah Braimah; Williams Agyemang-Duah; Yujiro Sano; Nancy Osei-Kye; Florence Wullo Anfaara; Roger Antabe; Ebenezer Dassah (BMC, 2023)
Abstract The literature recognizes food insecurity as a barrier to access to health care services. However, we know very little about the association between food insecurity and unmet dental care needs among older people in Ghana. To address this void in the literature, this study uses a representative survey of adults aged 60 or older from three regions in Ghana to examine whether older people who experienced household food insecurity differently report unmet dental care needs in comparison to their counterparts without any food insecurity. We find that 40% of older adults reported unmet dental care needs. Results from logistic regression analysis show that older people who experienced severe household food insecurity were more likely to report unmet dental care needs, compared to those who did not experience any type of food insecurity, even after accounting for theoretically relevant variables (OR = 1.94, p < 0.05). Based on these findings, we discuss several implications for policymakers and directions for future research.